Ship resistance and powering prediction using Holtrop's method - Liu, Xue Lin (2016)
Ship resistance and power prediction is essential to designing a new ship, and there are various methods applicable. A common point among all these methods is that they are very complicated and laborious. With the advance technology available to us nowadays, this process can be shortened or rather simplified through the usage of computers. The main purpose of this project is to develop a software program to eliminate this problem. Holtrop’s Statistical Analysis method is utilized, as in comparison to the other options, it is more complete and closer to the actual results. This report provides a description on the different prediction methods, brief information on ship resistance and propulsion system and factors affecting ship’s power efficiency. Followed by elaboration on how computer algorithm program is designed to calculate the ship resistance and power, including some practical case studies. To make the system more orderly, the tabulating process is separated into two segments, resistance and propeller performance. This would also allow users to understand the format and calculation process more easily. The designed Microsoft Office excel sheet was tested through comparing it with the collected data on a commercial ship. The results show that the method is plausible but still requires adjustment, in order to achieve higher accuracy and allow users to get results closer to practical cases.